SCA14 in Norway, two families with autosomal dominant cerebellar ataxia and a novel mutation in the PRKCG gene - Koht, J.; Stevanin, G.; Durr, A.; Mundwiller, E.; Brice, A.; Tallaksen, C. M. E. (Acta neurologica Scandinavica, 2012)
Koht J, Stevanin G, Durr A, Mundwiller E, Brice A, Tallaksen CME. SCA14 in Norway, two families with autosomal dominant cerebellar ataxia and a novel mutation in the PRKCG gene.  Acta Neurol Scand: 2012: 125: 116–122.  © 2011 John Wiley & Sons A/S. Objectives –  Despite a similar prevalence of autosomal dominant cerebellar ataxia (ADCA) in Norway compared to other European countries, less than 10% of the families are explained by the CAG trinucleotide expansions. We wanted to find the occurence of SCA14 in the dominant ataxia population and describe the phenotype. Methods –  We screened a large dominant cerebellar ataxia cohort for mutations in the PRKCG gene. Patients were evaluated according to a standard clinical protocol for ataxia patients. Results –  A novel mutation was found in two families, a C to A transversion altering Histidine to a Glutamine at codon 139, located in a highly concerved region in the gene. It completely co‐segregated with the affected family members and was not seen in 576 control chromosomes. Genetic analysis revealed common alleles at three microsatellite markers between these two families suggesting a shared ancestral chromosome. Affected subjects displayed a mild, slowly progressive cerebellar syndrome that included gait and limb ataxia and saccadic pursuit and head tremor in one. Age at onset ranged from 10 to 45 years. Conclusions –  These are the first families with SCA14 reported from Scandinavia and a new mutation in the PRKCG gene. The occurrence in the Norwegian dominant ataxia cohort is 3.5%.